Early recurrence and progression of a rare rectal squamous cell carcinoma after initial response to primary chemoradiotherapy. Issue 3 (May 2013) - Hogan, Niamh M; Leonard, Gregory; Sheehan, Margaret; Joyce, Myles R
Rectal squamous cell carcinomas represent an extremely rare malignancy which carries a significant morbidity and mortality. Diagnosis requires distinction from squamous cell carcinoma of the anus and colonic adenocarcinoma by endoscopy and histopathological examination of a biopsy. Due to the rarity of the pathology, available evidence is limited and optimum management has yet to be elucidated. Older reports favored radical surgical management, but recent reports in the literature recommend judicious use of primary chemoradiotherapy. We herein report the diagnosis and management of a male patient with an aggressive, locally advanced rectal squamous cell carcinoma treated with good results with primary chemoradiotherapy. Six months after completion of therapy, however, extensive recurrence and metastases were diagnosed. This case highlights the need for stringent clinical and radiological follow-up.